2012
DOI: 10.1111/j.1365-2605.2012.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the vitamin D metabolizing enzyme CYP24A1 at the annulus of human spermatozoa may serve as a novel marker of semen quality

Abstract: Vitamin D (VD) is important for male reproduction in mammals and the VD receptor (VDR) and VD-metabolizing enzymes are expressed in human spermatozoa. The VD-inactivating enzyme CYP24A1 titrates the cellular responsiveness to VD, is transcriptionally regulated by VD, and has a distinct expression at the sperm annulus. Here, we investigated if CYP24A1 expression serves as a marker for VD metabolism in spermatozoa, and whether CYP24A1 expression was associated with semen quality. We included 130 men (53 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 39 publications
(99 reference statements)
2
50
0
Order By: Relevance
“…In vitro studies showed that VDR induction mediated increased intracytoplasmic calcium in spermatozoa, resulting in increased motility and concomitant induction of the acrosomal reaction in capacitated sperm [16]. Furthermore, expression of VDR and CYP24A1 (a cytochrome P450 hydroxylase enzyme) in the annulus of sperm have been linked to all semen parameters, with higher expression of CYP24A1 associated with increased sperm motility in fertile compared to subfertile men [17]. However, two separate cross-sectional studies performed 1 year later failed to show a significant association between low serum vitamin D levels and poor semen quality [18,19].…”
Section: Male Reproductionmentioning
confidence: 99%
“…In vitro studies showed that VDR induction mediated increased intracytoplasmic calcium in spermatozoa, resulting in increased motility and concomitant induction of the acrosomal reaction in capacitated sperm [16]. Furthermore, expression of VDR and CYP24A1 (a cytochrome P450 hydroxylase enzyme) in the annulus of sperm have been linked to all semen parameters, with higher expression of CYP24A1 associated with increased sperm motility in fertile compared to subfertile men [17]. However, two separate cross-sectional studies performed 1 year later failed to show a significant association between low serum vitamin D levels and poor semen quality [18,19].…”
Section: Male Reproductionmentioning
confidence: 99%
“…The favourable effect of 25(OH) on human spermatozoa has been shown in vitro [26-28] and three cross-sectional association studies on serum 25(OH)D levels and semen quality have been conducted in young healthy men without infertility problems [27,29,30]. The results, however, were quite discordant (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…1b) [125, 127, 128]. Subcellular VDR expression may therefore depend on optimal spermatogenesis and maturation, because incomplete formation of the subcellular compartments may lead to an unusual localisation and, potentially, an unusual function of the receptor [132, 133]. …”
Section: α25(oh)2vitamin D3 (125-d3)mentioning
confidence: 99%
“…Moreover, 1,25-D 3 increased sperm motility and induced acrosome reaction [145]. 1,25-D 3 effect on motility was dependent on the characteristics of samples as 1,25-D 3 significantly increased spermatozoa motility in young men but was unable to do so in spermatozoa from sub-fertile men [133]. …”
Section: α25(oh)2vitamin D3 (125-d3)mentioning
confidence: 99%